2004
DOI: 10.1002/j.2161-1920.2004.tb00872.x
|View full text |Cite
|
Sign up to set email alerts
|

high anxiety: counseling the job‐insecure client

Abstract: In today's workplace, employees are faced with the potential of corporate downsizing, mergers and acquisitions, and job restructuring and relocation. These trends create a sense of job insecurity for the individual. Job insecurity affects the individual's life in a variety of ways, including emotional and psychological consequences, marital and family consequences, and organizational consequences. This article presents an overview of the effects of job insecurity and strategies that counselors can use in worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…It has also been suggested that conceptualizations of wellbeing at work (and in general) should include a component of social relationships, as this is a key component of an individual's positive experiences at work (Fisher, 2014). Research shows that employees with a high level of wellbeing put greater thought and effort into their work (Canaff and Wright, 2004; Keyes and Grzywacz, 2005; Day and Randell, 2014). Poor psychological health, such as depressed mood, anxiety and fatigue, are related to decrements in cognitive resources, and increased focus on negative or irrelevant information (Ford et al, 2011), which in turn is related to poorer performance (Taris, 2006).…”
Section: Wellbeing At Workmentioning
confidence: 99%
“…It has also been suggested that conceptualizations of wellbeing at work (and in general) should include a component of social relationships, as this is a key component of an individual's positive experiences at work (Fisher, 2014). Research shows that employees with a high level of wellbeing put greater thought and effort into their work (Canaff and Wright, 2004; Keyes and Grzywacz, 2005; Day and Randell, 2014). Poor psychological health, such as depressed mood, anxiety and fatigue, are related to decrements in cognitive resources, and increased focus on negative or irrelevant information (Ford et al, 2011), which in turn is related to poorer performance (Taris, 2006).…”
Section: Wellbeing At Workmentioning
confidence: 99%
“…Westman, Etzion and Danon (2001) studied this 'crossover' effect and found a direct crossover from husbands to wives but not viceversa, while Westman and Vinokur (1998) found a bi-directional crossover effect. Canaff and Wright (2004) point out that job insecurity may affect communication between spouses, causing strained parent-child relationships. Leisure activities and family life can thus become dysfunctional.…”
Section: Perceived Relationship Between Job Insecurity and Burnoutmentioning
confidence: 99%
“…In the literature, a high level of wellbeing has been reported to be associated with motivated employees, low rates of turnover, less absenteeism, greater work engagement and fewer work-related injuries (e.g. Canaff and Writh, 2004; Day and Randell, 2014; Keyes and Grzywacz, 2005). Future studies should measure these outcome variables in the context of art-of-living training in addition to measuring occupational self-efficacy in order to more comprehensively examine the effects of this type of training on work-related variables.…”
Section: Overall Discussionmentioning
confidence: 99%